PERANCANGAN RANGKA PADA ALAT PENYIMPANAN BARANG - Muhammad Yunus (Jurnal Surya Teknika, 2020)
Currently the development of universities in Indonesia is very fast both in quality and infrastructure. To help increase the security of important items being carried, goods storage devices are needed. Storage tools are designed to help put things in so that they are comfortable and not afraid of loss. The design of the frame on the goods storage device by calculating the strength of the welded joint on the frame. The storage frame for the goods is designed in three levels with a size of 162 cm (length), 56 cm (width), and 168 cm (height). By using NDT analysis and the frame material used is rectangular perforated iron with a size of 30 x 30 x 1 mm. All loads on the frame including the cover plate of the frame are assumed to be 100 kg. Then the theoretical calculation is obtained the weld strength is 0,047N/. The calculation result is still below the safety figure.